2021
DOI: 10.1136/ijgc-2021-002601
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation versus radiation alone in stage IIIB cervical cancer patients with or without human immunodeficiency virus

Abstract: ObjectiveCervical cancer remains the most common cancer among women in sub-Saharan Africa and is also a leading cause of cancer related deaths among these women. The benefit of chemoradiation in comparison with radiation alone for patients with stage IIIB disease has not been evaluated prospectively in women living with human immunodeficiency virus (HIV). We assessed the survival of chemoradiation versus radiation alone among stage IIIB cervical cancer patients based on HIV status.MethodsBetween February 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…HIV was not found to be associated with OS in this cohort of cervical cancer patients receiving antiretroviral therapy. Although prior studies from this region have reported worse survival among women with HIV, our current data aligns with our findings from previous studies which found no difference in OS by HIV status (Grover et al, 2018;Grover et al, 2021;MacDuffie et al, 2021). We hypothesize that the women living with HIV in our cohort have well-managed HIV which likely contributes to both their ability to tolerate treatment and their OS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…HIV was not found to be associated with OS in this cohort of cervical cancer patients receiving antiretroviral therapy. Although prior studies from this region have reported worse survival among women with HIV, our current data aligns with our findings from previous studies which found no difference in OS by HIV status (Grover et al, 2018;Grover et al, 2021;MacDuffie et al, 2021). We hypothesize that the women living with HIV in our cohort have well-managed HIV which likely contributes to both their ability to tolerate treatment and their OS.…”
Section: Discussionsupporting
confidence: 90%
“…patients, baseline factors associated with survival such as hemoglobin > 10 g/dL were consistent with our prior studies in patients treated with curative intent (Grover et al, 2018;Grover et al, 2021;MacDuffie et al, 2021). This suggests the significance of hemoglobin in indicating overall performance status of the patient and ability to receive adequate treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our previous work has shown no difference in OS between WLWH on ART and women without HIV who initiated curative chemoradiation treatment. 12,14,15 In our current study, the 2-year overall survival rates were lower for WLWH receiving RT only compared with women living without HIV; however, when adjusting for confounding factors including radiation dose, stage, and hemoglobin, there was no significant difference.…”
Section: Discussioncontrasting
confidence: 60%
“…Specific to CC, use of concurrent chemotherapy and brachytherapy improved survival, the type of brachytherapy (low v high dose rate) had no impact, and baseline anemia worsened survival. 36 , 56 , 79 , 81 , 83 , 85 - 88 One multinational study notes nearly identical survival compared with 20 years before. 33 Specific to BC, a lack of human epidermal growth factor receptor 2–targeted agents, large subset of triple-negative and/or undifferentiated tumors, and expensive chemotherapy worsened survival.…”
Section: Resultsmentioning
confidence: 99%